Identification of Weeds in Rice Crops (Oryza sativa L.) in the Wonco Rice Fields, Bungi Subdistrict, Baubau Town - Erin Amalia Putri; Jumiati; S. Hafidhawati Andarias (UNIVERSITAS KHAIRUN, 2026)
Weeds are one of the main factors that inhibit the growth and yield of rice crops in agricultural areas. The presence of uncontrolled weeds can compete with the main crop for resources, thereby significantly reducing productivity. This study aims to identify the morphological characteristics and types of weeds in rice fields (Oryza sativa) in the Wonco rice field area. The study consists of three stages: site observation, sample collection and data gathering, and identification. Data collection was conducted using an exploratory method, which involved exploring a rice field plot of 515 m². Weed sampling was conducted four times at various stages of rice plant growth. Identification was performed qualitatively based on morphological characteristics and quantitatively by calculating the percentage of weed presence. Environmental factors measured included air temperature, air humidity, soil temperature, soil humidity, pH, and light intensity. Based on the research conducted in the rice fields of Wonco, Bungi District, Baubau City, there are 40 species of rice weeds, consisting of 8 (eight) species of grasses, 6 (six) species of sedges, and 26 species of broad-leaved weeds.